Extravascular papillary endothelial hyperplasia of the larynx: a case report and review of the literature - (:unkn) unknown (My University, 2005)
Papillary endothelial hyperplasia (PEH), a tumor that falls along the spectrum of reactive to neoplastic vascular lesions, must be diagnosed carefully because it can resemble an angiosarcoma. PEH is generally considered to be the result of an unusual form of thrombus organization, exhibiting excessive papillary endothelial proliferation that is usually confined to the lumen of preexisting vessels or vascular malformations. Most cases of PEH are of the intravascular type; extravascular PEH is rare. We describe what we believe is the first reported case of an extravascular PEH in the larynx.
Keywords: Adult; Humans; Male; Hemangioendothelioma; Laryngeal Neoplasms